Peran Pengetahuan Keluarga dalam Meningkatkan Kemampuan Perawatan Pasien Gangguan Jiwa Berbasis Komunitas - Puji Kurniati (Jurnal Siti Rufaidah, 2025)
Mental disorders constitute a significant public health issue that necessitates family support in daily caregiving processes. This study aims to analyze the relationship between family knowledge levels and their ability to care for family members with mental disorders at the Neglasari Community Health Center (Puskesmas) in Tangerang City. This quantitative research employed a cross-sectional design and involved 45 respondents selected through total sampling. Data were collected using structured questionnaires on knowledge (Guttman scale) and caregiving ability (Likert scale), and were analyzed using univariate and bivariate methods through the chi-square test. The findings revealed that 51.1% of families had low levels of knowledge, while 40% were assessed as unable to provide adequate care. Bivariate analysis demonstrated a significant association between family knowledge and caregiving ability (p = 0.009). These findings suggest that family health literacy plays a crucial role in enhancing the quality of care for individuals with mental disorders. The implementation of family psychoeducation programs in primary healthcare settings is therefore essential to improve both knowledge and caregiving skills within home-based care. This study contributes to the development of community-based mental health services and provides a foundation for further research on educational interventions and family support systems.